Environmental Research Translation: Enhancing Interactions with Communities at Contaminated Sites - Ramirez-Andreotta, Monica D. (2014)
The characterization and remediation of contaminated sites are complex endeavors fraught with numerous challenges. One particular challenge that is receiving increased attention is the development and encouragement of full participation by communities and community members affected by a given site in all facets of decision-making. Many disciplines have been grappling with the challenges associated with environmental and risk communication, public participation in environmental data generation, and decision-making and increasing community capacity. The concepts and methods developed by these disciplines are reviewed, with a focus on their relevance to the specific dynamics associated with environmental contamination sites. The contributions of these disciplines are then synthesized and integrated to help develop Environmental Research Translation (ERT), a proposed framework for environmental scientists to promote interaction and communication among involved parties at contaminated sites. This holistic approach is rooted in public participation approaches to science, which includes: a transdisciplinary team, effective collaboration, information transfer, public participation in environmental projects, and a cultural model of risk communication. Although there are challenges associated with the implementation of ERT, it is anticipated that application of this proposed translational science method could promote more robust community participation at contaminated sites.